Indek Matos-Carvalho sebagai Perbandingan dengan Indeks Diskriminan Lain pada Talasemia Beta Awal - Mulyadi, Mulyadi; Mulyati, Mulyati; Ratnaningsih, Tri; Harahap, Nur Imma; Lesmana, Indra; Handayani, Niken Satuti Nur (Fakultas Kedokteran Universitas Trisakti, 2024)
Background Microcytic hypochromic anemia is the most common type of anemia found in Beta Thalassemia Trait and Iron Deficiency Anemia, posing a diagnostic challenge due to their similar presentations. Diagnostic errors among them can lead to incorrect treatment, potentially resulting in fatal outcomes. In Indonesia HPLC (High Performance Liquid Chromatography) usage as gold standard for discrimination between these diseases are expensive. Discrimination indices offer an alternative for cheaper and effective initial screening. However, a comprehensive performance evaluation of those indices, such as Matos and Carvalho indices, alongside Mentzer index, Green and King index, England and Fraser index, RBC index, Shine and Lal index, and Srivastava index, has not been conducted in Indonesia. This study aims to determine the best discriminative performance index based on the highest Youden’s indes value between those seven indices. Methods Study consisted of 30 subjects of beta thalassemia trait and 35 subjects of iron deficiency anemia. Index calculations were performed using blood profile formulas and compared with gold standard test results to find each index sensitivity, specificity, and Youden’s index value. Results Matos and Carvalho indices exhibited superior discriminatory performance, achieving 80% sensitivity, 77.1% specificity, and a Youden's index of 57.14%. Among other indices, the RBC index demonstrated the highest sensitivity (90%), while the Green and King index excelled in specificity (97.14%). MCV and MCH values did not significantly differ between BTT and IDA groups. Conclusions The study's findings underscore the efficacy of Matos and Carvalho indices in discriminating BTT and IDA in this study population, highlighting their potential as valuable tools in initial screening efforts.